Nitrofurantoin-Induced Neutropenia: A Case Report - Rajaram, Subashini; Mohandass, Subhalakshmi; Ravi, Priyadharsini; Murthy, Peethi Bala Dhakshina; Singam, Ann Jency Arul Durai (Indian Journal of Pharmacy Practice)
This case study describes the clinical course of a 60-year-old woman who presented to the general medicine department with a fever, body aches and a headache. Initial examination revealed fever, slightly elevated blood pressure and abnormal hematological parameters suggestive of dengue fever and Urinary Tract Infection (UTI). The patient tested positive for dengue NS1 antigen and exhibited urinary abnormalities consistent with UTI. Treatment comprised a regimen including nitrofurantoin for UTI, among other medications. Despite the intended treatment for UTI, the patient experienced adverse effects, notably neutropenia, as evidenced by a significant decline in neutrophil count. This adverse reaction underscores the importance of vigilant monitoring of patients on nitrofurantoin therapy to detect and manage potential complications promptly. Adjustments to the treatment plan may be necessary to mitigate risks and optimize patient care. This case highlights the critical need for clinicians to remain vigilant for adverse reactions, particularly in patients with comorbid conditions or complex medical histories. Effective management of adverse drug reactions is paramount to ensuring patient safety and therapeutic efficacy.
Keywords: Dengue fever; Urinary Tract Infection (UTI); Nitrofurantoin; Adverse drug reaction; Neutropenia; NS1 antigen; Hematological parameters; Patient safety; Therapeutic efficacy; Blood count monitoring; Treatment adjustment; Clinical management